Quality improvement in electrodeposition process of commercial vehicle using PDCA approach - Nabiilah, Ab Rahim (2018)
In a competitive world, the goals are best quality, shortest production time, and lowest cost. The main issues in meeting these three aspects are reducing cost and improving quality. In this research, a case study using a systematic approach and an application of basic and advanced tools and techniques was carried out in an actual automotive plant to improve the quality of the painting process. In the manufacturing of commercial vehicles, the problem faced was low quality of the painted body. A light commercial vehicle company was facing a low-quality problem on the electrodeposited surface of their product. The surface of the painted body was contaminated with defects during the electrodeposition process. The defect surface can be removed through the process of sanding but it is high in cost and requires extensive production time. The objectives of this study are to identify and analyse factors affecting the quality of electrodeposition process and reduce the operational cost. The study focused on reducing defects in the electrodeposition process of painting process to improve the quality and replacing the major sanding process with light sanding process. The PDCA cycle approach was utilised to reduce the defects in the electrodeposited body. The approach was proposed as it fitted the organisation culture adapted from the Japanese manufacturing management system. The major defect in the electrodeposited automobile bodies was identified by Pareto chart. The main defect of bits was investigated in this study. The major contribution of the bits was 80% from iron and 20% from phosphate. The iron filings from the metal assembly process carried out in the body assembly shop remained on the body during the painting process in the paintshop. The phosphate sludge was generated due to the effect of the chemical reaction with the metal and zinc phosphate chemical. Using quality tools like brainstorming, cause-and-effect diagram, and genba investigation, the root causes of the bit problem were identified. Through the Gravity, Urgency, and Tendency (GUT) analysis, the root causes were prioritised and the improvement activities were planned using 5W2H tools. The best method to prevent the bit defects was by removing or reducing the iron filing and phosphate sludge at the body assembly and painting departments. The process control, efficient filtration and spraying method, magnetic separation, and surface adjustment process were recommended to improve the bit defects. The application of PDCA cycle succeeded in helping the company to minimise from 103 to less than 21 bits per unit and contributed to a total of 49% operational cost reduction. The amount is equivalent to the salary of seven (7) operators at electrodeposition sanding line for one year. The results from the study have provided an insight on the successful deployment of PDCA cycle through the application of basic and advanced tools and techniques as the systematic problem-solving framework on solving actual industrial issues such as automotive painting problem.